Cross-cultural collaboration Wiki - Schadewitz, Nicole; Zakaria, Norhayati (2009)
In this paper, we propose a novel approach to share and develop knowledge of cross-cultural collaboration.Observations of cross-cultural collaborations in Hong Kong/Korean, Hong Kong/Austrian and Hong Kong/Taiwanese teams were captured using design patterns.These findings were posted to a Wiki, allowing further evaluation of the design patterns in different collaboration contexts.This process is discussed in the light of authorcentric and community-centric development of design patterns for cross-cultural collaboration.